А. М. Кутузов в 1790 году: Чтение, авторство, публичность [Aleksei Kutuzov in 1790: Reading, Authorship, Publicity] - Larionov, Oleg (Slavica Revalensia, 2023)
By focusing on a close reading of some passages from the letters of Rosicrucian and translator Aleksei Kutuzov, this paper reconstructs his reading strategies and ways of thinking about contemporary literature and public culture. The paper demonstrates that in his reading and writing habits Kutuzov depended heavily on the widespread early modern practice of commonplacing. In the early 1790s, Kutuzov constructed his arguments, construed the world, navigated current events and criticized Nikolai Karamzin’s project of a literary journal, as well as the whole modern public sphere and print culture, by quoting moral sententiae taken from the journal Guardian (1713) and other works perceived as edificatory reading.